2009
DOI: 10.1002/cphc.200800862
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Effects in Photoelectron Circular Dichroism of Alaninol

Abstract: A photoelectron circular dichroism (CD) study of the valence states of 2-amino-1-propanol (alaninol) in the gas phase is presented. The aim of the investigation is to reveal conformer population effects in the valence-state photoelectron spectrum. The experimental dispersion of the dichroic D parameter of valence states as a function of the photon excitation energy is compared with its theoretical value calculated by employing a multicentric basis set of B-spline functions and a Kohn-Sham Hamiltonian. The theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 25 publications
5
63
0
3
Order By: Relevance
“…We attribute this enhanced geometry dependence of b 1 to its incorporating the sine of the relative partial wave-scattering phases, these being most rapidly varying for small phase shifts differences1115. Subsequently, combined experimental/theoretical studies have confirmed a pronounced sensitivity of the PECD effect to molecular conformation1718192728.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We attribute this enhanced geometry dependence of b 1 to its incorporating the sine of the relative partial wave-scattering phases, these being most rapidly varying for small phase shifts differences1115. Subsequently, combined experimental/theoretical studies have confirmed a pronounced sensitivity of the PECD effect to molecular conformation1718192728.…”
Section: Discussionmentioning
confidence: 78%
“…The parameters are therefore a much more sensitive probe of photoionization dynamics than both the regular anisotropy parameter, (containing a limited phase information, and that then depends on the even cosine function) and especially the cross-section, σ (which contains no phase information). Consequently, b 1 measurements can be used to probe molecular geometry and structures16, including conformers17181920 and chemical substitution21. PECD seems, therefore, as an ideal tool to study also the dynamic interplay between electronic and nuclear motions upon photoionization.…”
mentioning
confidence: 99%
“…Dynamic effects of valence states in CDAD photoelectron spectroscopy have been recently studied for alaninol in gas phase from experimental and theoretical point of view. 34 The average magnitude of A CDAD parameters founded for alaninol adsorbed on Cu(100) is higher than those measured for free alaninol 34 and for molecules adsorbed on surface in the cases of alanine on Cu(110) and 2,3-butanediol on Si(100) for C 1s core level. [20][21][22] We studied the effect of the angular dependence on the dichroic parameters in the scattering plane defined by the [011] surface direction and the surface normal (see inset of Figure 1a).…”
Section: -25mentioning
confidence: 77%
“…CH 3 ) produces significant changes in the sign and/or magnitude of the circular dichroism. [34][35][36] In conclusion, we have investigated, by using circular dichroism in the angle distribution of valence photoelectrons, the chiral electronic features of the extended 2D domain of chiral selfassembled molecular structure originating from the adsorption of L-and D-alaninol on Cu(100).…”
Section: -25mentioning
confidence: 99%
“…Nowadays, PECD in the one-photon ionization of outer electrons is a well-established research area, which includes studies of molecular dimers [14], clusters [15], metal-organic complexes [16], and even small biological molecules [17][18][19][20]. Experimentally, this effect has been studied by tunable circularly polarized synchrotron radiation utilizing different methods of angle-resolved photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%